The artistic uniqueness of the novels of African-American writer Tony Morrison (Eurasian Research Bulletin, 2022)
Nobel laureate in literature whose best-selling work explored black identity in America — and in particular the often-crushing experience of black women — through luminous, incantatory prose resembling that of no other writer in English, died on Monday in the Bronx. She was 88.